Successful Elite Sport Policy in Sultanate of Oman: Sports Policy Factors Leading to Olympic Sporting Success (SPLISS-OMAN) - Alkindi, Ismail Issa (Πανεπιστήμιο Πελοποννήσου, 2024)
The study is descriptive research on the knowledge of an international project started in 2002 that compares sports policy to identify sports policy factors that lead to international sports success. The main objective of the present is to provide a detailed description of sports policies in Sultanate of Oman to determine the policies that lead Omani sports towards success in improving its sports system and achieving its vision of becoming a leading country in sports by 2040. The mathematical policy is analyzed from the theoretical model of De Bosscher et al. (2006), in which the factors affecting sports policy are categorized into nine pillars (financial support, organization and structure of sports policies, sports participation, the system for identifying and developing talents, sports, post-career support, training facilities, training and development of coaches, national and international competitions, scientific research and Innovation), to collect information on each pillar, a survey of athletes, coaches, and managers was prepared to "measure" the sporting climate in Sultanate of Oman. The results describe the sports policy developed in Sultanate of Oman for each specific pillar. These are presented in three sections: 1. What is being developed, 2. Concept of athletes and coaches, 3. Strengths and opportunities.
Keywords: Αθλητισμός και κράτος - Ομάν; Αθλητισμός - Διοίκηση και οργάνωση - Ομάν; Αθλητικές εγκαταστάσεις - Διοίκηση και οργάνωση - Ομάν; Αθλητισμός - Χρηματοοικονομική - Ομάν; Sports and state - Oman; Sports Management - Oman; Sports facilities - Management - Oman; Sports - Finance - Oman; Sports politics; Sports success; High-level sports; Spliss